Penerapan Prinsip Khalalan Toyyibah Dalam Mengonsumsi Prodak - wardani, Anggun kusuma; Yellse; Auliya, Septi; Yuristianti, Fitry Indah; Syafitri, Ghefira Zakia (Journal of Economics and Business, 2025)
This research aims to explore the Khalalan Toyyibah principles in the context of product consumption using a qualitative approach, through in-depth analysis of related literature. The research method used is library research with analysis of secondary data from various sources such as books, journals and related publications. The results show that the application of the Khalalan Toyyibah principle provides broad benefits and has a significant positive impact, including ensuring the consumption of food that is halal, healthy and beneficial for the body according to religious teachings, improving individual and collective health, as well as ensuring cleanliness, justice and continuity of the production chain. and distributing food. However, there are challenges in its implementation, such as higher production costs, time constraints, and minimal socialization and community participation in maintaining the sustainability of local halal food. In conclusion, joint efforts from various parties are needed to overcome these challenges and strengthen the implementation of the Khalalan Toyyibah principles for holistic, spiritual and social welfare in Muslim society. Penelitian ini bertujuan untuk mendalami penerapan prinsip Khalalan Toyyibah dalam konteks konsumsi produk dengan pendekatan kualitatif, melalui analisis mendalam terhadap literatur terkait. Metode penelitian yang digunakan adalah library research dengan analisis data sekunder dari berbagai sumber seperti buku, jurnal, dan publikasi terkait. Hasilnya menunjukkan bahwa penerapan prinsip Khalalan Toyyibah memberikan manfaat yang luas dan dampak positif signifikan, termasuk memastikan konsumsi makanan yang halal, sehat, dan bermanfaat bagi tubuh sesuai ajaran agama, meningkatkan kesehatan individu dan kolektif, serta mempromosikan kebersihan, keadilan, dan keberlanjutan dalam rantai produksi dan distribusi makanan. Namun, terdapat tantangan dalam implementasi, seperti biaya produksi yang lebih tinggi, keterbatasan waktu, dan minimnya sosialisasi dan partisipasi masyarakat dalam menjaga keberlangsungan pangan halal lokal. Kesimpulannya, diperlukan upaya bersama dari berbagai pihak untuk mengatasi tantangan tersebut dan memperkuat penerapan prinsip Khalalan Toyyibah demi kesejahteraan holistik, spiritual, dan sosial dalam masyarakat Muslim.